PENGARUH KUALITAS LAYANAN, REVIEW ONLINE TERHADAP KEPUTUSAN PEMBELIAN TIKTOK - I Ketut Raka Saputra; Putu Putri Prawitasari; Kadek Adyatna Wedananta; Anak Agung Gde Putra Pemayun (POLITEKNIK LP3I JAKARTA, 2025)
At this time, technology and information are increasingly sophisticated and increasingly experiencing very rapid growth. Commercial online platforms have emerged as one of the key pillars in the midst of the global commerce ecosystem in the rapidly expanding electronic age. One of the newest companies in the e-commerce space, Tiktok Shop, takes a different tack by fusing social media with online buying. defining a number of research projects, such as research models and mechanisms-based research methodologies, through data collection and testing. Reference sources must be used to support the definition of a research plan in order for the presentation to be accepted by academics. Using a quantitative approach, this study was carried out in Denpasar City, Bali, with a target demographic of Tiktok users who are familiar with and use Tiktok Shop. With 112 respondents, the sample was drawn via incidental sampling, a method for selecting samples at random or inadvertently. An online questionnaire measuring purchasing decisions, service quality, and online customer reviews using a grading scale was used to gather primary data. The SEM-PLS technique was used to analyse the data using Smart-PLS software, which included hypothesis testing, structural model evaluation (inner-model), and assessment (outer model). where the findings demonstrate that service quality significantly and favourably influences consumers' decisions to buy. Purchase decisions are also positively and significantly impacted by the influence of online consumer reviews.